Cancellation of Notary Deed Based on Agreement of The Parties Through Deed of Cancellation - Amalia, Thalita Reizky; Soroinda, Disriani Latifah (Fakultas Syariah INSURI Ponorogo, 2024)
An authentic deed is a form as written evidence that has perfect evidentiary power or so called fautless evidence. A deed can be declared as an authentic deed if it fulfil all the terms in article 1868 of Burgerlijk Wetboek, where the deed is made in the presence of or made by public functionary, namely a notary. As a public functionary that has an authority and obligations that clearly regulated in law, when carrying out his duties a notary must follows the notary’s act and the Code of Ethics. A notarial deed cannot be canceled immediately but must go through the correct process to remove the binding status of the deed. This research was conducted to provide an understanding of the proper and correct ways for cancellation of notarial deeds that can be carried out by the parties. The research methods that uses is doctrinal research methods, with secondary data which is divided into 3 legal materials, namely, primary, secondary and tertiary which are analyzed to answer the problems in the thesis. A deed made by a notary has binding legal force for each parties in the deed, as well with regulated third party in the deed. By the process, a deed can be invalidated or annulled if it does not fulfil the formal or material terms, either based on a lawsuit by one of the parties through a the decision of a court from judge, or based on the mutual agreement of the parties through a deed of cancellation.